Factors driving the demand for contemporary art amongst individual buyers in South Africa - Roberts, Ann (My University, 2021)
The purpose of this study is to investigate the motivations of individual contemporary art buyers in South Africa, in order to inform strategies for sustainability within the sector. The study reviews the nature and state of the contemporary South Africa art world and theories that attempt to explain the development of taste and actor behaviour in the field. An initial online survey reported a difference between the motivations of black and white buyers and therefore in-depth interviews were conducted with black buyers to understand these differences. White buyers’ motivations were revealed to align with those reported from the global north, with detracting factors being market opacity and information asymmetry. These factors were found to be barriers for all potential entrants into the field. The study shows how the dominance of western notions of what is legitimate culture and what is valid contemporary art, along with the impact of colonisation and Apartheid on the psyche and education of black buyers, has led to fewer black buyers entering the market. This study reveals that, those who do buy, are finding a Third Space and using their art buying activities to assert the importance and legitimacy of their own African cultural capital. It offers an understanding of the importance of African cultural capital for buyers within the context of the South African art market that will assist art world practitioners to strategise sustainability
A dissertation submitted in partial fulfilment of the requirement for the degree of Master of Arts (Cultural Policy and Management) in the University of the Witwatersrand, Johannesburg, Faculty of Humanities, 2021